BILATERAL PNEUMOTHORAX IN LUNG METASTASES OF BREAST CARCINOMA: A CASE REPORT - Kusdjianto, Amanda Yuanita; Samsuri; Andri; Andi, Wijayanto; Agus, Subiyantoro; Adi, Habibie (International Journal of Radiology and Imaging, 2022)
Introduction: Bilateral pneumothorax is a rare case which happens in 1.3 to 1.9 percent of all cases ofÂ  pneumothorax.1 In breast carcinoma patients, it is due to lung metastasis and first selected conservative therapy.2 Lung metastasis can be found in the appearance of pulmonary nodules called cannon-ball metastases in chest X-Ray (CXR).3 Method: Case report based on findings in chest X-Ray. Result: A 42 year-old female came to ER with sudden shortness of breath and pleuritic pain. She was diagnosed with breast carcinoma 3 years prior the ER visit and had undergone mastectomy on breasts and chemotherapy. Physical examination showed bilaterally decreased breath sounds. CXR AP postion showed bilateral pneumothorax and multiple nodules varied in size indicated lung metastases. Chest tubes with water-sealed drainage were inserted in both side of the lungs. CXR after the insertion showed reduction of the volume of pneumothorax in both side of the lungs and cannon-ball metastases in both sides of the lungs. CXR was performed serially until hospital discharge. Discussion: Bilateral pneumothorax which develops in patients who have history of breast carcinoma is considered very rare.It is caused by the metastatic process and treatment.2 CXR can be used to detect the metastasis and its complications such as pneumothorax.4 Conclusion: Bilateral pneumothorax is rarely seen in patients with breast carcinoma. Early detection of lung metastasis and appropriate therapy of tumor can prevent complications such as pneumothorax.Keywords: bilateral pneumothorax; lung metastases; breast carcinoma; chest X-Ray